Forced Convection Laminar Pulsating Flow in a 90-deg Bifurcation - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Khodadadi, Jay M. (Asme, 2021)
Numerical investigation of laminar forced convection of pulsating flow in a 90-deg bifurcation was performed with the finite volume method. The inlet velocity varies sinusoidally with time while constant wall temperature is utilized. The working fluid is air with constant properties and the numerical work is conducted for a range of the Reynolds numbers (100-2000), dividing flowrates (0.3-0.7) and Strouhal numbers (0.1-10). It is observed that the amplitudes of oscillating heat transfer are damped as the value of the Strouhal number increases. The average value of Nu number rises for higher Reynolds number and the dividing flowrate for the downstream wall of the y-channel branch. As the value of the dividing flowrate increases from 0.3 to 0.7, heat transfer is less effective in the vicinity of the branch at the Reynolds number of 500. The effects of the Reynolds number on the average Nu number variation is more pronounced for the y-branch wall for different values of dividing flowrates. Resonant type behavior of average Nu number is obtained for the y-branch channel for diving flowrates of 0.3 and 0.5.
Keywords: forced convection; heat transfer enhancement; pulsating flow; branching flow